THE FEASIBILITY OF TAPIOCA INDUSTRY IN DESA SERI TANJUNG, TANJUNG BATU, OGAN ILIR, SOUTH SUMATERA PROVINCE - Yesi, Desri; Natalia, Beta (Publikasi Penelitian Terapan dan Kebijakan, 2018)
This study examines the feasibility of tapioca industry in Ogan Ilir from the aspect of raw material availability, market potential, and profit/ loss projection so that it can give recommendation to the government in supporting the downstream of cassava especially tapioca flour industry. Data sources are primary and secondary data. The location was conducted in Desa Seri Tanjung, Tanjung Batu , Ogan Ilir, South Sumatera Province. The data analyzed by manually and computerized, and presented by descriptive quantitative. From the results of data processing, it was found that the tapioca industry in Ogan Ilir had a production capacity of 60 tons of tapioca flour per year or the need for tapioca raw materials of 240 tons per year that can be fulfilled by Ogan Ilir which recorded 310,05 tons. With this production capability, the industry is able to meet all the market needs of tapioca in Ogan Ilir, and can even meet nearly 40 percent of the need for tapioca flour in South Sumatera Province. From the financial side, Break Even Point is obtained for Rp. 341,246,269 or tapioca amounting to 31,022 kg. Internal Rate Return value of 14.41%, Net B / C 1.01 and Pay Back Period for 3 years.